Mithuna sculptures on mancha - Temples of India Project Team (Jio Institute, 2024)
Couples invoking shringara rasa (associated with romance, love, and attractiveness between lovers) are framed in panels with pillars and tiered shikhara with gavashka (horseshoe) motifs. The face of the female figure is missing and the face of the male figure is defaced. They are wearing heavy jewellery, elaborate headgear, and garments, indicating they are a royal couple. The central male figure and female figures are enjoying a musical concert in a grove. They are seated on circular raised seats; the male is in a lalitasana pose. The female figure is leaning towards the male and playing a stringed musical instrument (likely a veena). They are surrounded by four smaller figures. A male soldier is holding a sword and shield (on the left). One musician is playing the flute (bottom), sitting between the seats. A small female attendant is (top right) whispering in the ear of the central female. Mangoes hang from the tree branches.